32.9k views
4 votes
V(x)= x(8.5-2x)(11-2x) solve for v

1 Answer

2 votes

Answer:

V = 93.5x -39x2 + 4x3

Explanation:

Simplifying

V = x(8.5 -2x)(11 -2x)

Multiply (8.5 -2x) * (11 -2x) ,

V= x( 8.5*11 - 2x*8.5 -2x*11 - 2x* -2x)

V = x(93.5 - 17x - 22x + 4x2)

Combine like terms: -22x + -17x = -39x

V= x( 93.5 - 39x + 4x2)

Open the bracket by multiplying by x

V = (93.5 * x -39x * x + 4x2 * x)

V = (93.5x -39x2 + 4x3)

Solving for variable 'V'

V = 93.5x -39x2 + 4x3

User Smoove
by
4.8k points